2021
DOI: 10.7717/peerj.11895
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C core antigen test as an alternative for diagnosing HCV infection: mathematical model and cost-effectiveness analysis

Abstract: Background The cost and complexity of the polymerase chain reaction (PCR) test are barriers to diagnosis and treatment of hepatitis C virus (HCV) infection. We investigated the cost-effectiveness of testing strategies using antigen instead of PCR testing. Methods We developed a mathematical model for HCV to estimate the number of diagnoses and cases of liver disease. We compared the following testing strategies: antibody test followed by PC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Mathematical models have been extensively employed to study the role of HIV [4,[24][25][26][27][28][29][30][31][32][33][34], HCV [35][36][37][38] and STI [30,39] testing for the epidemic course and public health interventions. They all found that frequent testing is central to epidemic elimination [4,24,25,27,34].…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical models have been extensively employed to study the role of HIV [4,[24][25][26][27][28][29][30][31][32][33][34], HCV [35][36][37][38] and STI [30,39] testing for the epidemic course and public health interventions. They all found that frequent testing is central to epidemic elimination [4,24,25,27,34].…”
Section: Introductionmentioning
confidence: 99%